2002
DOI: 10.2527/2002.8061629x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rumen protein degradability and supplementation frequency on performance and nitrogen use in ruminants consuming low-quality forage: cow performance and efficiency of nitrogen use in wethers2

Abstract: Two studies were conducted to determine the influence of CP degradability and supplementation frequency (SF) on ruminant performance and N efficiency. Treatments included an unsupplemented control (CON) and degradable intake protein (DIP; 82% of CP) or undegradable intake protein (UIP; 60% of CP) provided daily, every 3 d, or every 6 d. Seven wethers (36+/-1 kg BW) were used in the digestibility study with DIP and UIP treatments formulated to meet CP requirements. Eighty-four Angus x Hereford cows (512+/-42 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
84
1
18

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 22 publications
18
84
1
18
Order By: Relevance
“…Physiologically, the mature beef cow can be triggered to better capitalize on recycled N and/or AA conservation to either meet the needs or reduce the demands during times of limited nutrient supply. Data on the effectiveness of frequency of supplementation strategies for cows (Houston et al, 1999;Bohnert et al, 2002;Farmer et al, 2004a) but not heifers (Moriel et al, 2012) and on the ability of cows to adapt to environments in terms of energy use conservation (Keren and Olson, 2006a,b) also support the concept that the current 1996 Beef NRC does not adequately account for plasticity and adaptability of the mature beef cow in arid and semiarid range conditions. An improvement in the next Beef NRC would be a model that does not ignore the contribution of MP for energy needs rather than going toward lean tissue growth.…”
Section: Perspective On the Transition From Cp To Mp Supply And Demanmentioning
confidence: 91%
See 1 more Smart Citation
“…Physiologically, the mature beef cow can be triggered to better capitalize on recycled N and/or AA conservation to either meet the needs or reduce the demands during times of limited nutrient supply. Data on the effectiveness of frequency of supplementation strategies for cows (Houston et al, 1999;Bohnert et al, 2002;Farmer et al, 2004a) but not heifers (Moriel et al, 2012) and on the ability of cows to adapt to environments in terms of energy use conservation (Keren and Olson, 2006a,b) also support the concept that the current 1996 Beef NRC does not adequately account for plasticity and adaptability of the mature beef cow in arid and semiarid range conditions. An improvement in the next Beef NRC would be a model that does not ignore the contribution of MP for energy needs rather than going toward lean tissue growth.…”
Section: Perspective On the Transition From Cp To Mp Supply And Demanmentioning
confidence: 91%
“…The effectiveness for alternative frequencies of protein supplementation to beef cattle consuming low-quality forage (Houston et al, 1999;Bohnert et al, 2002;Currier et al, 2004a,b,c;Farmer et al, 2004a,b;Schauer et al, 2005) indirectly implicated N recycling as an important process of N conservation in extensive grazing systems. Indeed, Wickersham et al (2008) concluded that in cattle consuming low-protein forage-based diets, N recycling played a significant role in the effectiveness of the alternative frequency of supplementation strategies.…”
Section: Degradable and Undegradable Intake Proteinmentioning
confidence: 99%
“…Konsumsi BK pada kedua kelompok yang sama dikarenakan kedua kelompok mengkonsumsi jerami dan konsentrat dalam jumlah yang relatif sama, dengan bahan baku dan kandungan nutrien yang relatif sama pula, hanya dibedakan pada kandungan RDP dan RUP-nya. Sesuai dengan hasil beberapa penelitian sebelumnya bahwa penambahan tingkat RUP dalam pakan tidak memberikan pengaruh nyata terhadap konsumsi BK (Diaz-Royon et al, 2016;Aboozar dan Niazi, 2013;Lopez, 2012;Duarte et al, 2011;Ali et al, 2009;Broderick et al, 2009;Richardel, 2004;Bohnert et al, 2002;Dunlap et al, 2000;Greenfield et al, 2000;Hartwell et al, 2000).…”
Section: Hasil Dan Pembahasanunclassified
“…A mudança na frequência de suplementação tem sido estudada internacionalmente (BOHNERT et al, 2002;LOY et. al., 2008) e pode ser uma opção eficiente para reduzir tempo, trabalho e equipamentos relativos ao fornecimento de suplementos, sem causar I Programa de Pós-graduação em Zootecnia, Universidade Federal de Santa Maria (UFSM), Santa Maria, RS, Brasil.…”
Section: Introductionunclassified